STRUCTURAL-PETROLOGICAL TYPES OF GRANITOID FORMATIONS OF THE UKRAINIAN SHIELD: GENERAL INFORMATION AND AUTOCHTHONOUS FORMATIONS - Кирилюк , В.П.; Шевченко, О.М. (Institute of Geological Sciences, NAS of Ukraine, 2025)
Granitoids make up the most common group of rocks of the basement of the Ukrainian Shield. They have a long history of exploration and dismemberment. As a result, granitoids are well studied in material and geochronometric terms. But at the same time, the structural position of the majority of granitoid complexes is clearly insufficiently studied, and therefore the dismemberment of granitoids on the traditional petrographic and age (geochronometric) basis is constantly changing to this day. More unambiguous and reproducible dismemberment is possible on the previously proposed geological and formational basis with the selection of a separate pluto-metamorphic class of granitoid formations as a natural association of metamorphic and plutonic rocks (Kyrylyuk et al., 1979). For these formations, their structural position can be determined in relation to the structural floors of the megablocks, to the stratigenic metamorphic complexes that form the basis of these floors, and even to individual supercrustal formations. In turn, data on the relationship between granitoid formations and stratigenic complexes and formations provide additional grounds for understanding their origin. This approach made it possible to propose the selection of the following types of Precambrian granitoid formations of shields (Kyrylyuk, Svechnikov, 1994): plutonic-metamorphic autochthonous, paraautochthonous, paraallochthonous, and plutonic allochthonous formations. This division was used by us when compiling the “Overview tectonic map of the basement of the Ukrainian Shield” on a scale of 1:1,000,000. It is reflected in the legend of the map, and in this publication, a brief overview of the granitoid formations is given on the map, some general issues of dismemberment of granitoids of the Ukrainian Shield and the considered type of allochthonous pluto-metamorphic formations are covered. It was made on the example of the formations of the Podilskyi megablock, within which the autochthonous formations are best represented.